A pediatric patient with hyponatremic hypertensive syndrome without persistent hypertension in acute phase: A case report and review of literature. (November 2020) - Hinokuma, Nodoka; Sakurai, Shunsuke; Shiratori, Atsutoshi; Nagahara, Keiko; Abe, Yoshifusa; Shimizu, Takeshi; Fujii, Takanari; Mizuno, Katsumi; Tomita, Hideshi
Hyponatremic hypertensive syndrome is characterized by hypertension, hyponatremia, and hypokalemia due to unilateral renal artery stenosis. We herein report a 1-year-old hyponatremic hypertensive syndrome infant without persistent hypertension in the acute phase. On the ninth hospital day, his systolic and diastolic blood pressure increased up to 154–160 and 70–84 mmHg, respectively. Acute gastroenteritis and dehydration might transiently mask his hypertension. By percutaneous transluminal balloon angioplasty for right renal artery, his blood pressure finally normalized without antihypertensive drugs. We reviewed 23 previously reported pediatric patients with hyponatremic hypertensive syndrome under the age of 15 years. Including our patient, there are only three reports on hyponatremic hypertensive syndrome without persistent hypertension in the acute phase. Hyponatremic hypertensive syndrome is curable with proper diagnosis and timely intervention. Therefore, pediatricians should pay attention to the signs and symptoms associated with hyponatremic hypertensive syndrome, even if persistent hypertension was absent in the acute phase.